Paraplegia due to A Rare Spinal Metastasis of Hepatocellular Carcinoma: A Case Report - Nerissa Arviana; Hendra Gunawan; Nilna Nur Faizah; William Luth (Department of Neurology Faculty of Medicine Universitas Sebelas Maret, 2026)
Background: Paraplegia caused by spinal cord compression is a rare but serious condition that can occur in cancer patients, including metastasis from hepatocellular carcinoma (HCC). Hepatocellular carcinoma metastasis to the spine can compress the spinal cord, disrupt nerve function, and lead to motor and sensory impairment in the lower limbs, ultimately resulting in paraplegia. Case: An 86-year-old man presented with progressive weakness in both lower limbs. He had not previously complained of weakness; his family attributed it to the natural effects of old age. However, the patient frequently complained of low back pain that did not improve with analgesics. Further investigation of the lesion revealed sensory impairment equivalent to the T8 dermatome. A complete physical examination showed an enlarged liver without stigmata of liver disease. CT scan revealed an extradural lesion at the T4 region and a compression fracture at the T8 region. The patient then underwent ultrasonography (USG), which identified a hepatoma suggestive of hepatocellular carcinoma (HCC). Discussion: Spinal cord compression as an initial presentation of HCC is uncommon and often delays diagnosis, especially in the absence of typical liver symptoms. MRI played a key role in identifying the extradural mass. Early recognition and management are crucial in preventing irreversible neurological damage. Treatment may include corticosteroids, radiotherapy, or surgery to relieve symptoms and improve quality of life; however, the prognosis remains poor without prompt intervention. Conclusion: These findings highlight the importance of early detection and comprehensive management in cases of paraplegia due to HCC metastasis to minimize neurological complications and improve patient survival.